Network Science in Biblical Studies: Introduction - Czachesz, István (Annali di storia dell'esegesi, 2022)
This article introduces the special issue of ASE on network science and biblical studies. After a short presentation of network science and the concept of networks, the article discusses the application of network science in three domains: the natural and built environment of ancient Judaism and Christianity, the social networks of Jewish and Christian actors, and the analysis of textual corpora. In the next part, some technical terms of network science are clarified. The introductory article concludes with the presentation of the contributions to the special issue.